FE homogenized limit analysis code for masonry buildings - Milani, G. (2011)
In this paper, a FE homogenized limit analysis code for the collapse analysis of 3D masonry buildings subjected to horizontal actions is presented. In the code, masonry is modelled through a fictitious macroscopic homogeneous material. Masonry macroscopic mechanical properties are obtained by means of a recently presented equilibrated limit analysis approach performed on a suitable unit cell, which generates the entire structure by repetition. Masonry homogenised failure surfaces are then implemented in the 3D code here outlined. With respect to previously presented models, the algorithm allows to analyze real scale buildings for coupled in-plane and out-of-plane actions. The possible presence of steel, RC and ring beams is also considered introducing in the numerical model two-node beam elements. A relevant 3D structural example consisting of a masonry school subjected to horizontal actions is treated. Full sensitivity analyses and a comparison with results obtained with a commercial elasto-plastic software are also presented to validate the model proposed.